Digital Service Innovation as a co-production of socio-technical assemblages oriented toward servitization - Rodríguez, María Alejandra; Lepratte, Leandro; Yoguel, Gabriel; Rabetino, Rodrigo (Emerald, 2025)
Purpose Digitalization in precision agriculture incorporates state-of-the-art digital technologies. The transformation requires manufacturers to launch digital platforms and services. As a result, innovation ecosystems emerge. In turn, digital technologies introduce novelty into innovation processes. This socio-technical transition is critical to understanding Digital Service Innovation (DSI). Thus, it is necessary for a micro-founded analysis that biographizes the socio-technical assemblages between routines, artifacts and humans that emerge from DSI processes. Against this backdrop, this study aims to examine the co-production processes and the configuration of digital servitization ecosystems based on Routine Dynamics and Sociomateriality views and the DSI perspective. Design/methodology/approach The study builds on multiple in-depth case studies, including three precision agriculture machinery and services ecosystems. For each ecosystem, the biography of the co-production process of the technological solution that integrates different actors and artifacts as a sociomaterial assemblage is reconstructed. The qualitative data consist of in-depth interviews with managers in the case companies and stakeholders in each ecosystem. Three ecosystems were surveyed. Documentary information from websites and technical documents on the products and services were systematized and incorporated into the analysis as a form of triangulation. Findings The analysis of ecosystem biographies evidences that DSI processes involve co-production between routines, actors and artifacts. This co-production implies moving from technology transfer relationships to the co-production of technological solutions oriented to digital servitization. New actors, digital artifacts and changes in user practices emerge as translators of DSI processes toward digital servitization. Thus, the emergence of technological solutions must be understood as socio-technical assemblages. The firms develop digital artifacts that allow the DSI process. The role of digital service platforms and users is critical in co-production. Digital artifacts based on algorithmic technologies perform automation and augmentation routines. Originality/value The study provides a complementary viewpoint between DSI approaches and the literature on Routine Dynamics and Sociomateriality. It explains in a micro-founded perspective, and based on biographies of the emergence of DSI ecosystems, how the relationship between digital artifacts, human practices and routines become dynamic in the co-production of Technological Solutions. This perspective proposes that DSI processes are based on the co-production of socio-technical assemblages. Thus, sociomateriality is at the center of analyzing the role of artifacts and the networks of relationships they perform and configure with humans, generating strategies, organizational practices and heterogeneous routine dynamics.
Keywords: Servitization; Co-production; Sociomateriality; Digital Service Innovation; Routine dynamics; fi=Strateginen johtaminen|en=Strategic Management|